Spatially Filtered Ridge Regression Modeling to Find Out the Rice Production Factors in East Java, Indonesia - Vita Dewi Islami; Rahma Fitriani; Henny Pramoedyo (CommIT (Communication and Information Technology) Journal, 2020)
The research aims to model rice production in East Java using the Spatially Filtered Ridge Regression (SFRR) method and ensure that all violations of assumptions are resolved by knowing the direct and indirect effect of predictor variables. The data are secondary data sourced from the publication of Badan Pusat Statistik containing provincial food crop agriculture statistics in East Java and the 2018 publication of Dinas Pertanian Jawa Timur (literally translated as Agriculture Department of East Java). The data analysis process is done by RStudio and ArcMap 10.3 software. In the research, the observation unit is 38 regencies or cities in East Java. The analysis results show that SFRR with queen contiguity weighting can overcome spatial autocorrelation and multicollinearity in rice production data in East Java. As for the established model, the variables of rice field area, urea fertilizer, Phonska fertilizer, SP-36 fertilizer, and tractor have a significant effect on rice production. However, ZA fertilizer has no significant effect on rice production. Then, a large comparison of direct and indirect impacts for each predictor variable is also generated. Generally, direct impacts are greater than indirect impacts.